Pengaruh Motivasi Belajar Terhadap Prestasi Belajar Siswa pada Pelajaran Sejarah Kebudayaan Islam di MI Miftahul Huda Pondok Petir Bojongsari Depok - Adella Noviyanti; Eva Hulaifah; Nurhayati; Riawati Astuti; Agus Suryana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to determine the effect of motivation on student learning achievement in SKI lessons at MI Miftahul Huda Pondok Petir Bojongsari Depok. The method used in this research is a quantitative method. . The total population of this study was 160 students with a sample size of 24 taken from 15% of the population using an error rate of 5%. Sample selection used random sampling. The research results obtained a correlation value of 0.696 and the r table for n = 24 with a significance level of 5% obtained an r table of 0.388. It is clear that rcount is greater than rtable. With a determinant coefficient of 0.69622 = 0.485. Thus, motivation of 48.5% influences the learning achievement of class IV students at MI Miftahul Huda Pondok Petir Bojongsari Depok.